2019
DOI: 10.1103/physrevlett.122.116401
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Switchable and Tunable Rashba-Type Spin Splitting in Covalent Perovskite Oxides

Abstract: In transition metal perovskites (ABO3) most physical properties are tunable by structural parameters such as the rotation of the BO6 octahedra. Examples include the Néel temperature of orthoferrites, the conductivity of mixed-valence manganites, or the band gap of rare-earth scandates. Since oxides often host large internal electric dipoles and can accommodate heavy elements, they also emerge as prime candidates to display Rashba spin-orbit coupling, through which charge and spin currents may be efficiently in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…The spin texture can often be manipulated and even reversed by switching the electric polarization under external electric field, leading to an all-electric and non-volatile control of spin state [20][21][22][23][24] . Rashba effects were mainly discussed in non-magnetic lead halide perovskites [9][10][11][12][13][14][15][24][25][26][27][28] or non-magnetic ferroelectric semiconductors [20][21][22][23][29][30][31][32][33] . However, to the best of our knowledge, there are no studies on the spin texture in AFM HOIP ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…The spin texture can often be manipulated and even reversed by switching the electric polarization under external electric field, leading to an all-electric and non-volatile control of spin state [20][21][22][23][24] . Rashba effects were mainly discussed in non-magnetic lead halide perovskites [9][10][11][12][13][14][15][24][25][26][27][28] or non-magnetic ferroelectric semiconductors [20][21][22][23][29][30][31][32][33] . However, to the best of our knowledge, there are no studies on the spin texture in AFM HOIP ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…1(a) (i.e., without SOC); meanwhile, the band splittings incorporating both PODF and SDF (termed as spin splittings) are displayed in Fig. 1 2 we fit the energy levels around the L (L-line), ( -L line), and F (F -S 2 line) points and obtain the following spin-splitting parameters for R3c LaWN 3 bulk: ∼2.7 and ∼1.6 eV Å for bands around L [A and B in Fig. 1(b)], ∼0.13 and ∼0.08 eV Å for bands around [C and D in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Spin splitting in ferroelectric materials is attracting a great deal of attention because it offers the possibility of novel spintronic devices based on electric control of spin textures [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Recently, various ferroelectrics presenting large spin splittings have been proposed theoretically or synthesized, including GeTe [6], SnTe [7], hyperferroelectrics [10,12], halides [8], and iodide perovskites [11], and the recently discovered Bi 2 WO 3 [3], BiInO 3 [5], and HfO 2 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a doped InAs heterostructure, it was found that the Rashba SOC could be enhanced by a factor of 1.5 [11] by applying a gate voltage of a few volts, while enhancement of up to a factor of 6 could be obtained in an InAs quantum wire [12]. Ferroelectric Rashba materials [36][37][38] also hold out the prospect of having large, electrically controllable Rashba couplings. However, even if the Rashba coupling of a material can only be changed by a small amount, the method described here allows large values of spin-rotation to be achieved by letting a particle undergo several periods of Bloch oscillation, and allowing the rotation to accumulate.…”
Section: Discussionmentioning
confidence: 99%